Application of Probiotic Bacteria: A Novel Approach Towards Ensuring food Safety in Shrimp Aquaculture - Rahman, Shafiqur; Khan, Shakila N; Naser, M Niamul; Karim, M Manjurul (Journal of Bangladesh Academy of Sciences, 2009)
Shrimp export is the second largest exportable commodity in Bangladesh. However, frequent outbreaks of microbial diseases over the last few years challenged its prospect to flourish. The use of antimicrobial chemicals have led to the emergence of more virulent pathogens, with the eventual transfer of antimicrobial resistance to human pathogens. The use of beneficial bacteria (probiotics) to displace pathogens by competitive processes and to inhibit their proliferation is a better remedy than administering antibiotics. A good number of bacteria from rearing environment for shrimp aquaculture with potential probiotic activity in vitro have been isolated. Two approaches, the well diffusion method and co-culture experiments confirmed their probiotic nature. Their non-hemolytic property also ensured their safe mode for application in shrimp aquaculture. Once the effect is successfully translated in the culture ponds, this will be an eco-friendly, harmless approach to combat the disaster caused by bacterial infections without compromising the shrimp quality, thereby ensuring food safety in shrimp industries of Bangladesh. Key words: Probiotic bacteria, food safety, shrimp aquaculture, vibrios DOI: 10.3329/jbas.v33i1.2958 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 1, 139-144, 2009